The Family’s Educational Role in Promoting Linguistic Cybersecurity - Hazaymeh, Omar (International Journal of Applied and Scientific Research, 2024)
Linguistic cybersecurity has emerged as a critical concern because language is powerful instrument in the digital age. This paper aims to investigate linguistic cybersecurity and its implications in the contemporary digital age. The study will investigate the family’s role in enhancing linguistic cybersecurity awareness and practices by exploring the dimensions of linguistic cybersecurity, its threats, and how families can contribute to its promotion. It emphasizes the importance of education and technological literacy for the family as factors in enhancing linguistic cybersecurity. By examining the family’s role, the paper explores its importance in protecting individuals’ linguistic identity and security against linguistic cybersecurity threats. The paper concludes with the need for comprehensive education for families as key player in enhancing linguistic cybersecurity.